Pengaruh Kualitas Layanan, Citra Merek dan Kepercayaan terhadap Kepuasan Pelanggan Dompet Digital Gopay: (Studi pada Mahasiswa Universitas Budi Luhur Jakarta Selatan) - Yamin Firdaus; Yugi Setyarko (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to examine the influence of service quality, brand image, and trust on customer satisfaction. The data source used in this study is primary data obtained through the distribution of questionnaires. The population of this study consists of Gopay digital wallet users at Budi Luhur University, South Jakarta. The sampling technique used is nonprobability sampling, with a purposive sampling method, and the sample size was determined using the Lemeshow formula, resulting in 99 respondents. The data analysis tool used is SPSS version 22. The results of the study show that service quality, brand image, and trust have a significant effect on customer satisfaction.